Challenges and Solutions of Islamic Education in the Era of the Digital Revolution and Artificial Intelligence (AI) - Amalia Ramadhani; Syamsul Aripin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the challenges and formulate strategic solutions for implementing Islamic education in the era of the digital revolution and artificial intelligence (AI). The research method used is conceptual qualitative research with a library research approach. The research instruments consisted of academic literature sources, such as national and international scientific journals, books, and relevant online articles. Data analysis techniques were conducted descriptively and analytically to identify challenges and opportunities, and to formulate strategies for developing AI-based Islamic education. The results show that Islamic education faces five main challenges: the digital infrastructure gap, low digital literacy of educators and students, ethical and spiritual value issues, curriculum unpreparedness for technology integration, and the rise of digital disinformation. Strategic solutions found include strengthening the digital competence of Islamic Education teachers, reconstructing the curriculum based on AI ethics, developing digital etiquette, collaboration between educational institutions and the technology industry, and ethical policy governance in the use of AI. Thus, Islamic education needs to integrate technology creatively while        remaining grounded in Islamic values to remain relevant in the digital era.